Agricultural mechanization in Ghana: Is specialization in agricultural mechanization a viable business model? - Houssou, Nazaire; Diao, Xinshen; Cossar, Frances; Kolavalli, Shashidhara; Jimah, Kipo; Aboagye, Patrick Ohene (International Food Policy Research Institute, 2013)
The Government of Ghana (GoG) since 2007 has been providing subsidized agricultural machines to individual farmers and private enterprises established as specialized Agricultural Mechanization Services Enterprise Centers (AMSECs) to offer tractor-hire services to small-scale farmers across the country. Current demand in the country is primarily focused on land preparation services, especially plowing. This paper assesses whether AMSEC enterprises are a viable business model attractive to private investors. Using firm investment theory and field-based data on costs, revenues, and tractor efficiency, this research examines the profitability of specialized agricultural mechanization service provision with a focus on land preparation. Findings suggest that the AMSEC model is not a viable business model, even with the current level of subsidy. Low operational scale is the most important constraint to the profitability of investment in specialized agricultural mechanization service provision. With such a low operational scale, it is essential to consider various options for introducing low-cost, small tractors suited to the current farming scale in the country. Also, a used tractor model is one of the options available for policymakers in the country. Tractor-hire services can play an important role in transforming smallholder agriculture, but with heavy subsidies on big and costly tractors, the subsidy policy can distort supply chain development. As a result, many better-suited and lower-cost machines are unlikely to be introduced into local markets.